Digital Lean-Process Framework for Creative-Industry Efficiency (Case: Sipirok, Indonesia) - Ahmad Rizki Harahap; Ernita; Tri Martial; Sri Ariani Safitri; Tetty Tiurma Sipahutar (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study develops a community empowerment model for the creative economy by integrating local wisdom, education, institutional support, and technology while applying Value Stream Mapping (VSM) to reduce process inefficiencies affecting sustainable tourism. The research introduces Lean-based process optimization using engineering metrics such as cycle time, uptime, and defect ratio. Results indicate that Lean interventions reduced cycle time by 25.3%, increased uptime by 6.8%, and decreased waiting waste by 21.4%, reflecting significant operational improvements. A mixed-method approach combining Partial Least Squares Structural Equation Modeling (PLS-SEM) and VSM was employed. From 110 creative industry actors, 86 respondents were selected using the Slovin formula. The findings reveal that education and skills (β = 0.336), institutional support (β = 0.352), and local wisdom (β = 0.249) significantly improve product innovation, which subsequently enhances income (β = 0.409) and sustainable tourism (β = 0.579). Technology showed no significant effect (β = 0.130; p = 0.413). The study demonstrates that combining socio-cultural empowerment with Lean-driven process redesign can strengthen innovation, operational performance, and sustainability in rural creative economies.